Un label européen pour les produits alimentaires de montagne ? - Rob McMorran; Fabien Santini; Fatmir Guri; Sergio Gomez-y-Paloma; Martin Price; Olivier Beucherie; Christine Monticelli; Alexia Rouby; Delphine Vitrolles; Guillaume Cloye (Revue de Géographie Alpine)
Recent research has demonstrated significant demand for foods from Europe’s mountain areas; the production of these foods delivers significant positive externalities, despite producers facing greater constraints than their lowland equivalents. Existing markets often fail to account for these factors due to a lack of clear definition of mountain products. This research investigated the current and potential future role of food labelling and certification to support mountain food supply chains and sustainable mountain development, using expert/stakeholder interviews, spatial analysis, and email survey. Results demonstrate that existing EU Geographical Indication schemes are important for marketing mountain foods; however, they are less suitable for small-scale producers. National schemes for certifying mountain products have limited effectiveness, although considerable scope for enhancement exists. Recent EU legislation defining mountain products represents a considerable opportunity; however, challenges and potential trade-offs remain regarding the development of criteria on the location of supply chain stages and environmental factors, certification and control methods, and definition of mountain areas.